Water Reduction and Dihydrogen Addition in Aqueous Conditions With ansa‐Phosphinoborane. Issue 61 (31st August 2022) - Sorochkina, Kristina; Chernichenko, Konstantin; Zhivonitko, Vladimir V.; Nieger, Martin; Repo, Timo
Abstract: Ortho ‐phenylene‐bridged phosphinoborane (2, 6‐Cl2 Ph)2 B‐C6 H4 ‐PCy2 1 was synthesized in three steps from commercially available starting materials. 1 reacts with H2 or H2 O under mild conditions to form corresponding zwitterionic phosphonium borates 1‐H2 or 1‐H2 O . NMR studies revealed both reactions to be remarkably reversible. Thus, when exposed to H2, 1‐H2 O partially converts to 1‐H2 even in the presence of multiple equivalents of water in the solution. The addition of parahydrogen to 1 leads to nuclear spin hyperpolarization both in dry and hydrous solvents, confirming the dissociation of 1‐H2 O to free 1 . These observations were supported by computational studies indicating that the formation of 1‐H2 and 1‐H2 O from 1 are thermodynamically favored. Unexpectedly, 1‐H2 O can release molecular hydrogen to form phosphine oxide 1‐O . Kinetic, mechanistic, and computational (DFT) studies were used to elucidate the unique "umpolung" water reduction mechanism. Abstract : Water reduction and H2 activation by an ortho ‐phenylene‐bridged phosphinoborane compound are demonstrated. The mechanisms of these transformations are investigated using kinetic measurements and DFT calculations. Nuclear spin hyperpolarization is detected as a result of parahydrogen (para‐H2 ) activation by the phosphinoborane in the presence of water, proving the reversibility of water addition to this compound.